Innovation and Creativity in the Development of Merras Pariyugeh Batik as a Driver of Local Economy in Madura - Supriyanto Supriyanto (Journal of Economic Perspectives and Business Innovation, 2024)
Abstract This study aims to analyze the role of innovation and creativity in the development of Merras Pariyugeh Batik as a driving force for the local economy in Madura. Batik Merras Pariyugeh represents a form of local cultural heritage that has significant economic potential when supported by creative innovation in design, production processes, and marketing strategies. This research employs a qualitative descriptive approach, using data collected through observations, interviews with batik artisans and local stakeholders, and documentation studies. The findings indicate that innovation in motif development, color combinations, and the utilization of eco-friendly materials, combined with creative marketing through digital platforms, has contributed to increased product value and market reach. Furthermore, the development of Merras Pariyugeh Batik has positively impacted employment opportunities, income levels of artisans, and the preservation of local cultural identity. However, challenges such as limited access to capital, technology, and managerial skills remain obstacles to sustainable development. The study concludes that strengthening innovation capacity and creative collaboration among artisans, government, and private sectors is essential to enhance the competitiveness of local batik and to foster sustainable local economic growth in Madura. Keywords: innovation, creativity, batik, local economy, Madura